2018
DOI: 10.1021/acssuschemeng.8b05132
|View full text |Cite
|
Sign up to set email alerts
|

Facile Production of Mesoporous WO3-rGO Hybrids for High-Performance Supercapacitor Electrodes: An Experimental and Computational Study

Abstract: This work explored a promising supercapacitor electrode material (WO 3 -rGO hybrids) synthesized via a simplistic one-pot hydrothermal synthesis route. Various analytical studies (X-ray diffraction study, Raman spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, Brunauer−Emmett−Teller analysis) were employed in furtherance to explore the structural, morphological, compositional, and surface areal properties of the prepared materials. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 66 publications
0
58
0
Order By: Relevance
“…These enhancements usually arise from the synergistic effects between the carbonaceous materials and the TMDs. Samal et al described the synergistic effect observed in the WO 3 /rGO composite electrode as due to the charge transfer between WO 3 and rGO sheets . The hybrid electrode material made from pseudocapacitive VSe 2 , EDLC type reduced graphene oxide and carbon nanotube enhances the power density and the cyclic stability of the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…These enhancements usually arise from the synergistic effects between the carbonaceous materials and the TMDs. Samal et al described the synergistic effect observed in the WO 3 /rGO composite electrode as due to the charge transfer between WO 3 and rGO sheets . The hybrid electrode material made from pseudocapacitive VSe 2 , EDLC type reduced graphene oxide and carbon nanotube enhances the power density and the cyclic stability of the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…In the high frequency region, as the electrodeposition time increases, the intercepts with the real axis decrease gradually, which means the equivalent series resistance becomes lower. 21,22 When the electrodeposition time is 45 min, the equivalent resistance of the electrode is 0.66 U lower than those of the other electrodes. When the electrodeposition time exceeds 45 min, it can be seen from the low-frequency and high-frequency regions that excess MnO 2 aggregation prevents the transfer of ions/electrons, which reduces the electrochemical performance of the electrode.…”
Section: Characterization Of the Mno 2 /Znco 2 O 4 /G/nf Electrodementioning
confidence: 97%
“…The specific capacitance was calculated from CV and GCD were using by following equation (1) and (2) respectively. 13…”
Section: -Electrode Systemmentioning
confidence: 99%
“…In the field of mesoporous materials, carbon-based functional materials represent the most investigated electrode materials for energy storage applications due to their excellent electrochemical activity as well as other advantages, including low costs and environmental friendliness. 1 A gazillions of strategies have been attempted by choosing different precursors to design supercapacitor with pseudocapacitive electrodes of carbon and oxides of iron, 4-8 manganese, 9 cobalt 10 , vanadium, 11 ruthenium, 12 tungsten, 13 nickel 14 and mixed metals [15][16][17][18][19] for the enhanced electrochemical properties. 4 For carbon composite chemistry, activating agents (e.g ZnCl2, KOH, H3PO4, K2CO3) are used to enhance the surface area, unique porosities and activity which add an extra step in synthesis.…”
Section: Introductionmentioning
confidence: 99%